MANAJEMEN PENDIDIKAN BERBASIS NILAI ISLAM: STUDI PADA SEKOLAH DASAR KUTTAB IMAM SYAFI’I - Riswanto, Aji (Institut Ummul Quro Al-Islami Bogor, 2025)
This study examines the implementation of Islamic value-based management at SD Kuttab Imam Syafi'i, focusing on three main aspects: conceptualization, operationalization, findings reveal that the school successfully integrates national and Islamic curricula through a balanced approach (40% academic, 30% tahfizh, and 30% moral education). Key innovations include the adaptation of the classical talaqqi method into a modern, structured format and the consistent application of the principle